Effects of a plant cyclotide on conformational dynamics and destabilization of β-amyloid fibrils through molecular dynamics simulations - Kalmankar, Neha V.; Gehi, Bhuvaneshwari Rajendrakumar; Sowdhamini, Ramanathan (Frontiers in Molecular Biosciences, 2022)
Aggregation of b-amyloid (Ab) peptide is one of the hallmarks of Alzheimer’s disease (AD) which results in chronic and progressive neurodegeneration of the brain. A recent study by our group have shown the ability of cyclic disulfide-rich peptides (“cyclotides”) isolated from a medicinal plant, Clitoria ternatea, to inhibit the aggregation of Ab peptides and reduce oxidative stress caused by reactive oxygen species using in vivo models of transgenic Caenorhabditis elegans. In the present study, through extensive computational docking and multi-ns molecular dynamics (MD) simulation, we evaluated if cyclotides can stably bind to Ab molecules and/or destabilize the Ab fibril by preventing conformational changes from a-helical to b-sheet rich structures. We demonstrate that cyclotides bind effectively and stably to different forms of Ab structures via hydrogen bonding and hydrophobic interactions. One of the conserved hydrophobic interface residues, Tyr10 was mutated to Ala and the impact of this virtual mutation was estimated by additional MD simulations for the wild-type (WT) and mutant protein-peptide complexes. A detailed MD simulation analyses revealed that cyclotides form hydrogen bonds with the toxic amyloid assemblies thereby weakening the inter-strand hydrogen bonds between the Ab peptide. The phi-psi distribution map of residues in the cyclotide binding pocket that ideally adopt b-sheet conformation show deviation towards right-handed a-helical (aR) conformation. This effect was similar to that observed for the Tyr10Ala mutant and doubly so, for the cyclotide bound form. It is therefore possible to hypothesise that the opening up of amyloid b-sheet is due to an unfolding process occurring in the Ab caused by cyclotide binding and inhibition. Our current findings provide novel structural insights on the mode of interaction between cyclotides and Ab fibrils and describe their anti-amyloid aggregation potential. This sheds light on the future of cyclotide-based drug design against protein aggregation, a hallmark event in many neurodegenerative diseases.